Finite Elements Method Simulation of P(VDF-TrFE) Piezoelectric Sensor for Internet of Things Application - KEAT, CHOW KHOON; Abdal Kadhim, Ali Mohammed; LEONG, KOK SWEE; TEE, LAU KOK (International Journal of Integrated Engineering, 2019)
This paper presents finite element method (FEM) simulation and internet of things application by using P(VDF-TrFE) piezoelectric sensor where there are mechanical vibration present on the piezoelectric material for batteryless sensors. Therefore, this simulation was conducted using COMSOL Multiphyisc 5.1 to study the resonance frequency, stress, displacement and load dependence for the P(VDF-TrFE) piezoelectric sensor. The optimized design of P(VDF-TrFE) piezoelectric sensor was tested in the step monitoring application by using the internet of things (IoT) system.